Spin contamination errors on spin-polarized density functional theory/plane-wave calculations for crystals of one-dimensional materials. (17th October 2019) - Tada, Kohei; Tanaka, Shingo; Kawakami, Takashi; Kitagawa, Yasutaka; Okumura, Mitsutaka; Yamaguchi, Kizashi
Abstract: An estimation scheme is established for the spin contamination error (SCE) in spin-polarized density functional theory calculations with the plane-wave basis for crystals of one-dimensional materials. The size consistency of the scheme was confirmed via H-chain models, and the accuracy was confirmed by the comparison with the reported experimental values. The scheme was applied to real systems, specifically, tribromo-trioxotriangulene and [Ni(cyclohexanediamine)2 Br]Br2 crystals. It clarified the SCEs on the energies of calculated models (0.049–3.093 eV). The presented scheme will enable the appropriate investigation and design of functional materials of nano (molecular) wire, superconductors, catalysts, quantum computing, and so on.